2001
DOI: 10.1088/0031-9155/46/3/320
|View full text |Cite
|
Sign up to set email alerts
|

Determining changes in NIR absorption using a layered model of the human head

Abstract: A theoretical approach is presented to determine absorption changes in different compartments of a layered structure from distributions of times of flight of photons. In addition resulting changes in spatial profiles of time-integrated intensity and mean time of flight are calculated. The capability of a single-distance, time-domain method to determine absorption changes with depth resolution is tested on a layered phantom. We apply this method to in vivo measurements on the human head (motor stimulation, Vals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 25 publications
2
200
0
Order By: Relevance
“…This is a reasonable assumption with regards to piglets and human neonates as their skulls are relatively thin, but a poor assumption with regards to adults (Cooper et al, 1996). It has been shown that over 50% of the illuminated tissue volume in adults can be comprised of extra-cerebral tissue (Steinbrink et al, 2001). This signal contamination has been shown to cause a significant underestimation of CBF, and presumably the same would apply to CMRO 2 (Gora et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is a reasonable assumption with regards to piglets and human neonates as their skulls are relatively thin, but a poor assumption with regards to adults (Cooper et al, 1996). It has been shown that over 50% of the illuminated tissue volume in adults can be comprised of extra-cerebral tissue (Steinbrink et al, 2001). This signal contamination has been shown to cause a significant underestimation of CBF, and presumably the same would apply to CMRO 2 (Gora et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4c, which shows comparable amplitudes for the same absorption change in two different locations. Further improvement in quantification requires better depth resolution, as can be provided by time-domain measurements (Kohl-Bareis et al, 2002;Steinbrink et al, 2001) or by prior spatial information from structural and functional MRI. Further discussion of time-domain methods for imaging brain activation falls outside of the scope of this paper.…”
Section: Partial Volume Errorsmentioning
confidence: 99%
“…The changes in oxygenation are calculated from changes in attenuation at different wavelengths. This spectroscopic approach can be applied to the intensity and the mean TOF data, which have been shown to be differentially sensitive to changes in deeper layers of the tissue (Steinbrink et al, 2001b). The oxygenation response typically expected over an activated cortical area consists of a -decrease in [deoxy-Hb], accompanied by an -increase in [oxy-Hb], of 2-to 3-fold magnitude, thus resulting in an -increase in total hemoglobin ([tot-Hb]).…”
Section: Physiology Of the Signalmentioning
confidence: 99%